2010
DOI: 10.1016/j.jep.2010.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Traditionally used Thai medicinal plants: In vitro anti-inflammatory, anticancer and antioxidant activities

Abstract: This study provides in vitro evidence for the use of the Thai plants, most importantly Gynura pseudochina var. hispida, Oroxylum indicum and Muehlenbeckia platyclada as Thai anti-inflammatory remedies and these plants are now a priority for further phytochemical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 70 publications
3
99
0
2
Order By: Relevance
“…In order to eliminate the influence of the moisture content of the plant, the yield of the extracts from B. alba leaves and T. terrestris seeds with different solvents were calculated depending on a dry weight basis and the yields were found to be high. Similar high yield from B. alba leaves has been reported with methanol in successive extraction with petroleum ether, ethyl acetate and methanol (Siriwatanametanon et al, 2010). Maximum yield percentage for T. terrestris seeds was obtained with aqueous extraction in a study using solvents such as petroleum ether, chloroform, acetone, alcohol and water (Asadulla 2011).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In order to eliminate the influence of the moisture content of the plant, the yield of the extracts from B. alba leaves and T. terrestris seeds with different solvents were calculated depending on a dry weight basis and the yields were found to be high. Similar high yield from B. alba leaves has been reported with methanol in successive extraction with petroleum ether, ethyl acetate and methanol (Siriwatanametanon et al, 2010). Maximum yield percentage for T. terrestris seeds was obtained with aqueous extraction in a study using solvents such as petroleum ether, chloroform, acetone, alcohol and water (Asadulla 2011).…”
Section: Resultssupporting
confidence: 58%
“…Aqueous and methanol extracts from the dry leaves of Basella alba, a fast growing vegetable, probably originating from India (Bamidele et al, 2010), has been reported to possess active components that increase testosterone production in adult male rat testes during in vitro studies (Moundipa et al, 1999;Moundipa et al, 2005). This edible plant has also been described to possess nutritional values including androgenecity in traditional medicines of several countries (Siriwatanametanon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Siriwatanametanon et al (2010) reported that the methanol extract of the fresh leaves of C. trifolia has more potent DPPH free radical scavenging activity and strongly inhibits lipid peroxidation compared with Pouzolzia indica. A significant difference at p<0.05 was found between the fresh and dried leaf samples using water extraction.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of the leaves of C. trifolia showed the highest antioxidant activity because of the high amount of phenolics, such as cyanic acid and cyaniding (Siriwatanametanon et al 2010). Maisuthisakul et al (2007) reported that phenolic compounds and its derivatives, such as phenolic acids and tannins, are strongly correlated with antioxidant activity.…”
Section: Tpcmentioning
confidence: 99%
“…Several inflammatory mediators, mainly bradykinin and metabolites of arachidonic acid, are potent pain-producing agents that can excite and sensitize nociceptive primary afferent neurons (Petho, Reeh, 2012). Several plant extracts have been studied for their anti-inflammatory properties, by using in vitro and in vivo models (Ojewole, 2006;Siriwatanametanon et al, 2010;Areej et al, 2013), and existing data suggest that L. divaricata may also have similar characteristics.…”
Section: Introductionmentioning
confidence: 99%